- Thread starter
- #1

$$ P_v=

\left\{

\begin{array}{ll}

a\left(\frac{b}{1+\exp\left(-\bar \mu\frac{P_s X}{r^\alpha}+\varphi\right)}-1\right), & \text{if}\ \frac{P_s X}{r^\alpha}\geq P_a,\\

0, & \text{otherwise}.

\end{array}

\right.

$$

**My Take:**

First, let's solve the equation for $P_v$. For that, let's assume g(x) to be:

$$g(x) = \frac{P^0}{\exp(\overline{\mu}P_{th} + \varphi)}\left( \frac{1+\exp(-\overline{\mu}P_{th} + \varphi)}{1 + \exp(-\overline{\mu}P_s x r^{-\alpha} + \varphi)} - 1\right),$$

Then,

$$

P_v = \begin{cases}

g(x) & x \geq \frac{P_{th}}{P_s}r^\alpha\\

0 & x < \frac{P_{th}}{P_s}r^\alpha

\end{cases}

$$

Then, with the knowledge that the PDF for Exponentially distributed RV is $f(x) = e^{-\lambda x}$ (with $\lambda = 1$ for our case), we can find $\mathbb{E}[P_v]$.

$$ \mathbb{E}[P_v]= \int_Q^\infty g(x)f(x)dx \ \ \ \ \ \ \ \ \ \ \ (1) $$

where $Q = \frac{P_{th} r^{\alpha}}{P_s}$.

**Is this method correct or am I making any mistake?**